Connexin 50 mutation lowers blood pressure in spontaneously hypertensive rat - Šeda, Ondřej; Liška, František; Pravenec, Michal; Vernerová, Z; Kazdová, Ludmila; Křenová, Drahomíra; Zídek, Václav; Šedová, Lucie; Krupková, Michaela; Křen, Vladimír (Physiological research, 2017)
We assessed the effect of the previously uncovered gap junction protein alpha 8 (Gja8) mutation present in spontaneously hypertensive rat - dominant cataract (SHR-Dca) strain on blood pressure, metabolic profile, and heart and renal transcriptomes. Adult, standard chow-fed male rats of SHR and SHR-Dca strains were used. We found a significant, consistent 10-15 mmHg decrease in both systolic and diastolic blood pressures in SHR-Dca compared with SHR (P<0.01 and P<0.05, respectively; repeated measures analysis of variance (ANOVA)). With immunohistochemistry, we were able to localize Gja8 in heart, kidney, aorta, liver, and lungs, mostly in endothelium; with no differences in expression between strains. SHR-Dca rats showed decreased body weight, high-density lipoprotein cholesterol concentrations and basal insulin sensitivity in muscle. There were 21 transcripts common to the sets of 303 transcripts in kidney and 487 in heart showing >1.2-fold difference in expression between SHR and SHR-Dca. Tumor necrosis factor was the most significant upstream regulator and glial cell-derived neurotrophic factor family ligand-receptor interactions was the common enriched and downregulated canonical pathway both in heart and kidney of SHR-Dca. The connexin 50 mutation L7Q lowers blood pressure in the SHR-Dca strain, decreases high-density lipoprotein cholesterol, and leads to substantial transcriptome changes in heart and kidney.
Keywords: hypertenze; Animals; Blood Pressure; mužské pohlaví; Connexins; konexiny; mutace; Rats; Gene Regulatory Networks; Heart; ledviny; játra; potkani inbrední SHR; krevní tlak; Liver; srdce; zvířata; Kidney; genové regulační sítě; Hypertension; Mutation; krysa rodu Rattus; Male; Rats, Inbred SHR